2022
DOI: 10.1007/s00068-022-02120-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Tracheostomy Well-Being Score in critically ill patients

Abstract: Purpose Little attention has been given to understanding the experiences and perceptions of tracheostomized patients. This study aimed to measure the impact of tracheostomy on well-being in critically ill patients with the development of the Tracheostomy Well-Being Score (TWBS). Methods This is a prospective, monocentric, observational study including critically ill patients with a tracheostomy without delirium. A 25-item questionnaire with items from six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Tacheastomy is one of the most commonly performed procedures in critical care, signi cantly impacting public health by facilitating long-term ventilation and airway management for patients with severe respiratory conditions (1). Globally, it is estimated that tracheostomy is performed in about 10-15% of those who receive mechanical ventilation in intensive care units (ICUs) (2). A comprehensive study by the Global Tracheostomy Collaborative (2021) Highlighted that the timing and outcomes of tracheostomy (typically within 7 to 10 days of mechanical ventilation) are associated with shorter ICU stay and improved survival rates (3).…”
Section: Introductionmentioning
confidence: 99%
“…Tacheastomy is one of the most commonly performed procedures in critical care, signi cantly impacting public health by facilitating long-term ventilation and airway management for patients with severe respiratory conditions (1). Globally, it is estimated that tracheostomy is performed in about 10-15% of those who receive mechanical ventilation in intensive care units (ICUs) (2). A comprehensive study by the Global Tracheostomy Collaborative (2021) Highlighted that the timing and outcomes of tracheostomy (typically within 7 to 10 days of mechanical ventilation) are associated with shorter ICU stay and improved survival rates (3).…”
Section: Introductionmentioning
confidence: 99%
“…2 From these studies, it was found that earlier tracheostomy placement can provide benefits in patients who require prolonged mechanical ventilation. [3][4][5] Several factors are known to influence the outcome in patients undergoing tracheostomy. Another study said that age and comorbidities affect the mortality rate in patients who underwent tracheostomy.…”
Section: Introductionmentioning
confidence: 99%